Utilizing Pometia Pinnata leaf extract in microwave synthesis of ZnO nanoparticles: Investigation into photocatalytic properties - Sulistyo Rini, Ari; Rati, Yolanda; Maheta, Gema; Aji, Arie Purnomo; Saktioto (Communications in Science and Technology, 2024)
In this work, ZnO photocatalyst has been synthesized using matoa (Pometia pinnata) leaf extract under various microwave irradiation powers at 360, 540, and 720 Watts for 3 minutes on each. The UV-Vis absorption spectra of ZnO exhibited a peak in the ultraviolet region 300-360 nm. UV-Vis absorption analysis revealed a decrease in the band gap energy from 3.15 eV to 3.10 eV as the irradiation power increased. Field emission scanning electron microscopy (FESEM) images displayed spherical and nanoplatelet morphology with a decrease in particle size observed from 773 to 709 nm with increasing irradiation power. X-ray diffraction (XRD) analysis confirmed the hexagonal wurtzite structure of ZnO with crystallite sizes in the range of ~18-20 nm. The synthesized ZnO nanoparticles was successfully employed as a photocatalyst in 4-nitrophenol degradation, achieving the highest degradation percentage of 82.7% at 540 Watts with a corresponding reaction rate constant of 0.0126/min. In conclusion, the microwave-assisted synthesis of ZnO using on matoa leaf extract demonstrated significant potential for the degradation of organic pollutants, thereby contributing to water purification efforts.